2004
DOI: 10.1309/b8tc0lbvh8xy5mfv
|View full text |Cite
|
Sign up to set email alerts
|

Immunostaining for Human Herpesvirus 8 Latent Nuclear Antigen-1 Helps Distinguish Kaposi Sarcoma From Its Mimickers

Abstract: We assessed the usefulness of a mouse monoclonal antibody (13B10) against human herpesvirus 8 (HHV-8) latent nuclear antigen-1 (LNA-1) in diagnosis of Kaposi sarcoma (KS) and for distinguishing it from various mimickers by studying 50 cases of KS and 53 mimickers (angiosarcoma, 15; kaposiform hemangioendothelioma, 6; spindle cell hemangioma, 3; reactive angioendotheliomatosis, 3; bacillary angiomatosis, 4; acroangiomatous dematitis, 2; microvenular hemangioma, 2; hobnail hemangioma, 2; pyogenic granuloma, 5; d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(42 citation statements)
references
References 16 publications
3
38
1
Order By: Relevance
“…We do not advocate diagnosis of Kaposi's sarcoma based on presence of the virus alone due to the possibility of finding HHV-8 in other types of lesions, a view shared by other investigators. 4,5 As to the second point, we agree with Pantanowitz et al that molecular methods can detect HHV-8 in non-Kaposi's sarcoma lesions. However, PCR-based detection methods for HHV-8 are very sensitive and can produce positive results due to the presence of 'bystander' virus contamination.…”
Section: Response To Pantanowitz Et Alsupporting
confidence: 90%
See 2 more Smart Citations
“…We do not advocate diagnosis of Kaposi's sarcoma based on presence of the virus alone due to the possibility of finding HHV-8 in other types of lesions, a view shared by other investigators. 4,5 As to the second point, we agree with Pantanowitz et al that molecular methods can detect HHV-8 in non-Kaposi's sarcoma lesions. However, PCR-based detection methods for HHV-8 are very sensitive and can produce positive results due to the presence of 'bystander' virus contamination.…”
Section: Response To Pantanowitz Et Alsupporting
confidence: 90%
“…Others have shown similar results, including in endemic Kaposi's sarcoma. [4][5][6] None of these studies reported HHV-8 serologic data. While this information would be useful, we believe it does not significantly detract from our overall conclusion that immunohistochemical demonstration of HHV-8 virus in tumor cells of vascular and spindle cell lesions is a useful tool (in association with histopathologic and clinical features) when the diagnosis of Kaposi's sarcoma seems reasonable.…”
Section: Response To Pantanowitz Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, three large studies, by Cheuk et al, 8 Robin et al 9 and Patel et al, 25 have shown LANA expression in 71 of 72 cases, 50 of 50 cases and 21of 21 of Kaposi sarcoma, respectively, as compared with 0% of non-Kaposi sarcoma potential mimics. All of the non-Kaposi sarcoma vascular tumors in these three studies occurred in HIVnegative individuals, except for four cases of bacillary angiomatosis in the study of Cheuk et al; 8 neither study examined HHV-8 positivity by PCR. The present study detected LANA expression in 92% of Kaposi sarcoma cases, a rate comparable to that seen in previous results.…”
Section: Discussionmentioning
confidence: 98%
“…5,6 A small number of studies have shown LANA expression to be specific for Kaposi sarcoma among vascular tumors occurring in the general population. [6][7][8][9] Evaluation of LANA expression has thus been proposed as an ancillary technique for the discrimination of Kaposi sarcoma from other vascular lesions with which it may be confused, such as stasis-associated vascular proliferations, spindle cell hemangioma, kaposiform hemangioendothelioma, and spindled variants of angiosarcoma. It is currently unknown, however, whether non-Kaposi sarcoma vascular lesions arising in immunocompromised patients might express LANA, possibly reflecting origin from an HHV-8-positive endothelial progenitor cell, or secondary HHV-8 infection.…”
mentioning
confidence: 99%